Growth and Development of Two Perennial Grasses in Ambient Light Conditions during their Natural Dormant Period. Issue 4 (25th May 2017) - Guo, Jia; Boe, Arvid; Kim, Do‐Soon; Lee, D.K.
Abstract : Phenological and morphological behaviors under variable temporal and spatial environmental conditions provide essential information for breeding native perennial warm‐season grasses for bioenergy and ecosystem goods and services. Among various environmental factors, natural photoperiodic signals can affect both vegetative and reproductive growth of perennial species. In this study, field‐collected plants of switchgrass ( Panicum virgatum L.) and prairie cordgrass ( Spartina pectinata Link) were subjected to ambient photoperiods of either increasing or decreasing daylength during the dormant period of their normal growth cycles in a temperature‐controlled greenhouse. Upland switchgrass reacted to a short‐day treatment (decreasing or increasing daylength <12 h) with a less synchronized dormancy‐breaking pattern than prairie cordgrass. Prairie cordgrass showed a strict daylength overriding dormancy‐breaking pattern. However, phenological and morphological traits observed during the growing season through reproductive development and senescence indicated that the capacity to reach sexual maturity for both species was not greatly affected by subjection to noninductive photoperiod immediately after breaking dormancy. Overall, our results indicated that switchgrass coped with unfamiliar natural photoperiod conditions better than prairie cordgrass in terms of vegetative and reproductive growth.